A RANDOMIZED PLACEBO CONTROL TRIAL TO ESTIMATE THE EFFICACY OF ORAL MIFEPRISTONE IN PRE-INDUCTION RIPENING OF CERVIX IN TERM PREGNANCY - Dr. Divyashree Bhat, Dr. Yogindrakumar M. Kabadi (South Eastern European Journal of Public Health, 2025)
Background: Cervical ripening is a crucial step in successful labor induction. Mifepristone has emerged as a potential pre-induction cervical ripening agent, but its efficacy needs further investigation. Objective: To evaluate the effectiveness of mifepristone for pre-induction cervical ripening by assessing changes in modified Bishop's score. Secondary objectives included comparing induction-to-delivery intervals, delivery modes, and neonatal intensive care unit (NICU) admission rates. Methods: This randomized, placebo-controlled trial was conducted at the Department of Obstetrics and Gynecology, Karnataka Institute of Medical Sciences, Hubballi, India. We enrolled 232 women with singleton term pregnancies (37-42 weeks gestation) and randomly assigned them to receive either 400mg mifepristone (Group A, n=116) or placebo (500mg calcium tablet) (Group B, n=116). Failed inductions received dinoprostone gel after 24 hours. Modified Bishop's scores were assessed at 0-, 24-, and 48-hours post-administration. Results: Group A demonstrated significant improvement in modified Bishop's score at 24 hours compared to placebo. Only 36% of mifepristone-treated patients required additional induction methods, and the induction-to-delivery interval was reduced by 26.3 hours compared to placebo. Cesarean section rates were comparable between groups. No significant differences in maternal or perinatal morbidity and mortality were observed between groups. Conclusion: Mifepristone demonstrates significant efficacy as a pre-induction cervical ripening agent in term pregnancies, reducing the need for additional induction methods and shortening the induction-to-delivery interval without increasing adverse outcomes.